Investigation of the Similarities of Industrial Wood Production Statistics of Regional Directorates of Forestry in Turkey Using Cluster and Discriminant Analysis - AKYÜZ, İlker; ERSEN, Nadir; BAYRAM, Bahadır Çağrı; ACAR, Mustafa; AKYÜZ, Kadri Cemil; ÜÇÜNCÜ, Tutku (Kastamonu University, 2019)
Aim of study: In this study, the amount of industrial wood production of the regional directorates of forestry in Turkey was examined deeply and the similarities between the regional directorates in industrial wood production were investigated by cluster and discriminant analysis. Area of study: The study area is regional directorates of forestry in Turkey. Material and Method: Seven different variables were used to construct similar clusters. The arithmetic mean of these seven variables was taken for 4 years (2013-2016).  Cluster and discriminant analysis were used as method. Main results: According to the clustering analysis results, it was determined that regional directorates of forestry could be divided into maximum 6 and minimum 2 groups. As a result of the discriminant analysis conducted to determine the highest success of the groupings, it was determined that the regional directorates of forestry distinguished in 100% success in 6 groups. Also, it was found that a Kastamonu regional directorate of forestry, which has the highest value in industrial wood production, has formed a group alone. Highlights: For the production of industrial wood, the regional directorates of forestry can put more emphasis on the use of forest areas. Thus, we can avoid the dependence on foreign sources.